Reconsidering Legal Personhood in Indonesian Private Law: Bundles of Legal Incidents, Attribution, and Governance Failure - Shidarta Shidarta; Febrian Febrian; Jeong Chun Phuoc (Sriwijaya Law Review, 2026)
Legal personhood is undergoing a profound conceptual shift as private law confronts claims involving nature and artificial intelligence. This article reconsiders legal personhood not as an ontological category but as a functional institutional device for allocating rights, duties, powers, liabilities, and immunities. It conceptualizes personhood as a point of attribution through which bundles of Hohfeldian legal incidents become operational in private-law relations and are translated into standing, enforceability, liability, and remedies. This article employs a doctrinal legal research method with a conceptual and analytical-jurisprudential orientation, combining Hohfeldian analysis with a structured comparative assessment. It examines the Atrato and Whanganui River models according to representational effectiveness, enforceability, remedial performance, and accountability allocation, and evaluates three design options for artificial intelligence: no personhood, limited personhood, and full personhood. Although centered on Indonesian private law, the analysis also considers transjurisdictional doctrinal and regulatory developments, particularly in Malaysia and the broader ASEAN region. The comparison indicates that personhood for nature operates effectively only when supported by workable representation, enforceable duties, and a concrete remedial architecture. For artificial intelligence, personhood is normatively justified only where it strengthens attribution and remedies without severing liability from the human and organizational actors who design, deploy, control, or benefit from AI systems. The article concludes that any expansion of legal personhood in Indonesian private law requires rigorous institutional justification and must not operate as a symbolic designation or liability shield.